Association between dietary sodium intake and non-alcoholic fatty liver disease in the US population - Zhou, Long; Yang, Yuxuan; Feng, Yang; Zhao, Xiaodan; Fan, Yameng; Rong, Jie; Zhao, Liancheng; Yu, Yan (Public health nutrition, 2021)
To explore the association between dietary Na intake and non-alcoholic fatty liver disease (NAFLD) in a nationally representative sample of the US population. In this cross-sectional study, the associations between Na intake and NAFLD, defined by the hepatic steatosis index (HSI) and the fatty liver index (FLI), were assessed through multivariable logistic regression models. Communities in the USA from 2007 to 2014. Men and women aged 20 years and older. A total of 11 022 participants were included in the HSI-defined NAFLD analysis, and a subsample of 5320 participants was included in the FLI-defined NAFLD analysis. Compared with the lowest quartile of Na intake, the highest quartile had a multivariate-adjusted OR and 95 % CI of 1·46 (1·29, 1·65) for NAFLD as defined by HSI, and 1·41 (1·18, 1·69) for NAFLD as defined by FLI. This association was, to some degree, attenuated but remained significant after adjusting for several related metabolic parameters, including BMI, hypertension, hypercholesterolaemia, and diabetes. Findings from the current study indicate that dietary Na intake is positively associated with NAFLD in US adults.